Lived Experiences of Public Elementary SLM Writers: Basis for the Development of a Training Program - Galang, Ruby T.; Balboa, Nina Rizza; Catu, Rheynalyn M.; Digneneng, Cyrene S.; Francisco, Angelica Nichole N.; Reyes, Sherlyn T. (Future Science / FSH-PH Publications, 2022)
The study aimed to explore the lived experiences of Public Elementary SLM writers in the new normal education who were required to write modules for various subjects in the elementary level and had difficulties in crafting the modules. The researchers made use of a qualitative approach specifically, descriptive phenomenology to understand the personal experiences of the key informants. A semi-structured online interview was conducted with the eleven selected key informants from various schools. The research study used the purposive sampling technique, open-ended questions as instrument, and data collected were analyzed using Colaizzi’s 1978 phenomenological method. Findings show mastery of content, creativity, time management skills, grammar skills, information and communication technology skills, good communication skills and flexibility are the skills needed to possess as a SLM writer. While the challenges and difficulties encountered are lack of training programs for SLM writers, difficulties in making suitable activities for learners, time constraint in writing modules, overlapping responsibilities, lay-outing difficulties, running out of ideas in content delivery, less proficiency in computer literacy. Different coping practices were also identified by collaboration among colleagues, utilizing academic peripheral resources, time management through priorities, devising ways for the improvement of modules content, and SLM writer’s motivation such as children's educational success and professional development success. The evaluators, criteria and common feedback received during evaluation of SLM were identified. SLM Writers addressed the feedback through considering and taking it as constructive ones. Researchers recommended training and webinars about writing modules. Writers should be resourceful to compensate for the shortcomings of their needs and the children.